SARS-CoV-2 Reverse Transcription-Polymerase Chain Reaction Positivity and Seroprevalence among Health Care Workers in a Referral Cancer Institute: A Cross-sectional Study - Zekri, Abdel-Rahman; Ahmed, Ola S.; Asem, Noha; Musa, Sherief; Ibrahem, Mohamed; Soliman, Hany K.; Hafez, Mohammed M.; Nessim, Margrit S.; Aboelkasem, Hatem; Bahnassy, Abeer A. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: During the ongoing coronavirus disease 2019 pandemic, healthcare workers (HCWs) are presumed to be at increased risk of infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), transmitting the infection to vulnerable patients if they are not timeously isolated. AIM: This study aimed to determine the point prevalence of SARS-CoV-2 infection in a cohort of HCWs providing oncology services. METHODS AND RESULTS: HCWs in a large referral cancer hospital in Egypt were tested using real-time reverse transcription-polymerase chain reaction (RT-PCR) on nasopharyngeal swabs, and immunochromatography-based rapid serological test (RST). Clinical and epidemiological data were collected. In 2020, 999 HCWs were screened, of whom 86 tested positive for SARS-CoV-2 by RT-PCR (8.6%) and 127 subjects were seropositive for antibodies against SARS-CoV-2 by RST (12.8%). Immunoglobulin M seroprevalence demonstrated considerable concordance with RT-PCR positivity (sensitivity 82.14% and specificity 96.71%). Most HCWs (>95%) reported adherence to personal protective equipment. Patient transporters/cleaner were the group with the highest frequency of positive RT-PCR (19%) whereas laboratory and radiology technicians displayed the lowest frequency. Fever, dry cough, rhinorrhea, shortness of breath, fatigue and diarrhea were significantly associated with RT-PCR positivity, with increased likelihood of being positive with the presence of five or six simultaneous symptoms. CONCLUSIONS: The point prevalence of SARS-CoV-2 infection in screened HCWs is 8.6% by RT-PCR and seroprevalence is 12.8% by RST. Strict measures should be implemented to minimize transmission within healthcare settings and to the community. Our data support the importance of HCWs screening for SARS-CoV-2, taking in account the significant proportion of asymptomatic carriers.